Various Methods of Holding Suction Tubes for Cerebral Aneurysm Surgery: Highlighting Tanikawa’s Technique - ศรีอมรรัตนกุล, กิติพร (Thai Journal of Neurological Surgery, 2025)
The author conducted a review of various methods for holding suction tubes during cerebral aneurysm surgery, detailing and demonstrating each technique. Additionally, the fundamental principles behind suction holding techniques were summarized. The author highlighted the specific method developed by Professor Rokuya Tanikawa, which may be particularly effective for cerebral aneurysm surgeries, especially in dissecting the Sylvian fissure and interhemispheric fissure. The discussion also included the advantages and disadvantages of this technique, along with its clinical applications.